LRRC6 Mutation Causes Primary Ciliary Dyskinesia with Dynein Arm Defects - Horani, Amjad; Ferkol, Thomas W.; Shoseyov, David; Wasserman, Mollie G.; Oren, Yifat S.; Kerem, Batsheva; Amirav, Israel; Cohen-Cymberknoh, Malena; Dutcher, Susan K.; Brody, Steven L.; Elpeleg, Orly; Kerem, Eitan (PloS one, 2013)
Despite recent progress in defining the ciliome, the genetic basis for many cases of primary ciliary dyskinesia (PCD) remains elusive. We evaluated five children from two unrelated, consanguineous Palestinian families who had PCD with typical clinical features, reduced nasal nitric oxide concentrations, and absent dynein arms. Linkage analyses revealed a single common homozygous region on chromosome 8 and one candidate was conserved in organisms with motile cilia. Sequencing revealed a single novel mutation in LRRC6 (Leucine-rich repeat containing protein 6) that fit the model of autosomal recessive genetic transmission, leading to a change of a highly conserved amino acid from aspartic acid to histidine (Asp146His). LRRC6 was localized to the cytoplasm and was up-regulated during ciliogenesis in human airway epithelial cells in a Foxj1-dependent fashion. Nasal epithelial cells isolated from affected individuals and shRNA-mediated silencing in human airway epithelial cells, showed reduced LRRC6 expression, absent dynein arms, and slowed cilia beat frequency. Dynein arm proteins were either absent or mislocalized to the cytoplasm in airway epithelial cells from a primary ciliary dyskinesia subject. These findings suggest that LRRC6 plays a role in dynein arm assembly or trafficking and when mutated leads to primary ciliary dyskinesia with laterality defects.